Effectiveness and Study of the Criminal Law Pretrial System - Laurensia Putri (Enigma Institute, 2023)
The pretrial system evaluation is a crucial procedure that seeks to assess the efficiency, equity, and durability of institutions created to safeguard the rights of individuals who are accused or defendants in criminal judicial procedures. This system is a vital component of the criminal justice system that specifically emphasizes the safeguarding of individual rights, the prevention of abuse, and the guarantee of procedural fairness. It is important to make sure that this system works well and lasts a long time so that there is a good balance between good law enforcement and protecting human rights under criminal law.